Evaluation of F8-TNF-α in Models of Early and Progressive Metastatic Osteosarcoma() - Robl, Bernhard (Transl Oncol, 2017)
The targeted delivery of tumor necrosis factor-α (TNF-α) with antibodies specific to splice isoforms of fibronectin [e.g., F8-TNF, specific to the extra-domain A (EDA) domain of fibronectin] has already shown efficacy against experimental sarcomas but has not yet been investigated in orthotopic sarcomas. Here, we investigated F8-TNF in a syngeneic K7 M2–derived orthotopic model of osteosarcoma as a treatment against pulmonary metastases, the most frequent cause of osteosarcoma-related death. Immunofluorescence on human osteosarcoma tissue confirmed the presence of EDA in primary tumors (PTs) as well as metastases. In mice, the efficacy of F8-TNF against PTs and early pulmonary metastases was evaluated. Intratibial PT growth was not affected by F8-TNF, yet early micrometastases were reduced possibly due to an F8-TNF–dependent attraction of pulmonary CD4(+), CD8(+), and natural killer cells. Furthermore, immunofluorescence revealed stronger expression of EDA in early pulmonary metastases compared with PT tissue. To study progressing pulmonary metastases, a hind limb amputation model was established, and the efficacy of F8-TNF, alone or combined with doxorubicin, was investigated. Despite the presence of EDA in metastases, no inhibition of progressive metastatic growth was detected. No significant differences in numbers of CD4(+) or CD8(+) cells or F4/80(+) and Ly6G(+) myeloid-derived cells were observed, although a strong association between metastatic growth and presence of pulmonary Ly6G(+) myeloid-derived cells was detected. In summary, these findings demonstrate the potential of F8-TNF in activating the immune system and reducing early metastatic growth yet suggest a lack of efficacy of F8-TNF alone or combined with doxorubicin against progressing osteosarcoma metastases.